Executive Dysfunction: A Contributor to Subtypes of Violence or General Criminality? - Hancock, Megan B (2014)
Purpose: The adverse consequences of violence on society are tremendous. Several factors have been identified as potential contributors to violent crime, including deficits in executive functioning. Executive functioning is a term used to a describe number of higher-order cognitive abilities (e.g., working memory, inhibition) that are thought to be essential for appropriate, socially desirable behavior. The extent to which executive functions influence the occurrence of general criminality versus specific subtypes of crime is largely unknown. Of particular interest is the ability of executive functioning to distinguish between reactive and instrumental subtypes of violence. Whereas reactive violence is committed with the intention of harming the victim after perceived provocation, instrumental violence is committed with the intention of obtaining some kind of goal other than inflicting injury. Hence, the purpose of this study was clarify the relationship between executive functioning and subtypes of criminal offending, as well as to clarify the convergent and divergent validity of different indicators of executive functioning within the context of understanding crime. Method: One hundred and fifty-one adult male inmates from a federal correctional facility participated in this study. Participants completed both performance-based and self-report measures of executive functioning and their complete criminal histories were reviewed. Results: Consistent with hypotheses, executive functions were differentially related to subtypes of offending. Moreover, findings suggested that (a) performance-based tasks and self-report measures of executive functioning are unrelated to one another and are differentially related to subtypes of crime, (b) it is important to examine separate components of executive functioning rather than a composite score, and (c) the relationships between executive functions and crime are not accounted for by general intelligence. Conclusion: Taken together, this dissertation demonstrated that executive functioning is most useful when using a crime-specific approach to understanding criminality. Future research should examine this relationship longitudinally to better understand whether this is a causal link or whether there are other pathways through which executive functioning influences the likelihood of an individual engaging in specific subtypes of violence. An understanding of the variables underlying different types of violence is a necessary precursor for risk assessment and offender rehabilitation